MANAJEMEN TATA KELOLA SUMBER DAYA ALAM BERBASIS PARADIGMA EKOLOGI POLITIK - WASISTO RAHARDJO JATI, WASISTO RAHARDJO JATI (Politika: Jurnal Ilmu Politik, 2012)
Abstract Developmentalism is still the dominant perspective in managing natural resources. Nature is strategic economic assets that sparked the exploration and exploitation of natural wealth. The implication is massive environmental damage in many places. Political Ecology emerged as alternative perspective in managing natural resources to build synergy between nature and human relationships through local wisdom. This paper will review briefly the prospects and challenges of political ecology as alternative paradigm in the natural resource management. Key Words : natural resource management; developmentalism; political-ecology; local wisdom